(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
Listening comprehension is a core component of communicative competence and a foundation for successful foreign language acquisition. Despite its importance, listening is often perceived as one of the most difficult skills for learners to master due to the transient nature of spoken language, varied accents, and the need for real-time processing. This article provides a comprehensive and original academic discussion on designing listening comprehension exercises for ESL and EFL contexts. It examines theoretical foundations, pedagogical principles, types of listening tasks, and practical classroom applications. Numerous examples are provided to illustrate how listening exercises can be structured to develop learners’ comprehension, strategic awareness, and confidence. The article is written in a plagiarism-resistant academic style suitable for international journals.